Pengaruh Gaya Kepemimpinan Transaksional, Penempatan Kerja dan Iklim Kerja Terhadap Kinerja Karyawan - Agusthina Risambessy; Paulus L Wairisal (IQTISHODUNA, 2021)
The problem of the quality of human resources is the most important part for every company, both government and private. This study aims to analyze and explain the effect of transactional leadership style on employee performance, job placement on employee performance and work climate on employee performance. This research is located at PT.Bank Modern Express Ambon. The research population is all permanent employees of PT.Bank Modern Express Ambon. The sample used is 94 people, using the saturated sampling technique. Multiple linear regression analysis methods. The results of the study prove that transactional leadership style with contingent reward indicators, active expectations management indicators, passive exception management indicators, have a significant positive effect on the performance of PT. Modern Express Bank Ambon. Work placement with indicators of education, skills, and physical and mental health has a significant positive effect on the performance of employees of PT. Modern Express Bank Ambon. Work climate using indicators of compensation, cooperation, work suitability, division of tasks, and organizational policies have a significant positive effect on the performance of employees of PT. Modern Express Bank Ambon.